1989
DOI: 10.1007/bf01799571
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine 5′‐nucleotidase activity in normal and deficient human lymphoblastoid cells

Abstract: Two distinct pyrimidine 5'-nucleotidases (UMPH-1 and UMPH-2) have previously been detected in human erythrocytes; UMPH-1 is deficient in a haemolytic anaemia, while UMPH-2 is unaffected. Only the erythrocyte shows pathological effects in this disorder. Here we have studied lymphoblastoid cell lines from control and UMPH-1 deficient patients to determine whether UMPH-1 can be detected in lymphoblastoid cells and whether the deficiency of UMPH-1 results in any measurable metabolic effects. Both UMPH-1 and a UMPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…This enzyme catalysis the dephosphorylation of 5' nucleotides and exists on the membranes of human peripheral-blood lymphoid cells. In some studies enzyme activity was measured in erythrocytes, T and B-lymphocytes, mononuclear and plasma cells (6,8,14). In our study 5' NT activity was determined in mononuclear cells.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This enzyme catalysis the dephosphorylation of 5' nucleotides and exists on the membranes of human peripheral-blood lymphoid cells. In some studies enzyme activity was measured in erythrocytes, T and B-lymphocytes, mononuclear and plasma cells (6,8,14). In our study 5' NT activity was determined in mononuclear cells.…”
Section: Discussionmentioning
confidence: 78%
“…In our study 5' NT activity was determined in mononuclear cells. As the analysis of enzymatic methods are different from previous studies we were unable to discuss our results with them (2,6). We preferred to use HPLC, as the method is 50-fold more sensitive than that based on calorimetric measurements and furthermore avoids the use of radioactive materials (2).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Most cells contain a number of different nucleotidases able to hydolyse pyrimidine monophosphates, which limits the effects of P5′N‐1 deficiency largely to the red cell. Nevertheless, it has been shown that in nucleated cells, P5′N‐1 deficiency results in abnormal pyrimidine nucleotide metabolism (Hopkinson et al , 1990).…”
Section: The Physiological Role Of P5′n‐1mentioning
confidence: 99%
“…For example, uridine monophosphate can be used as a substrate and the rate of uridine released by the action of P5′N‐1 quantified by HPLC (Simmonds et al , 1991). Other diagnostic techniques include electrophoretic analysis of P5′N isozymes, demonstrating an absence of functional P5′N‐1 protein (Hopkinson et al , 1990), and nuclear magnetic resonance spectroscopy of P5′N‐1‐deficient red cells, which shows a diagnostic spectrum due to the accumulation of cytidine diphosphate (CDP)‐choline, pyrimidine nucleotides, CDP‐ethanolamine and uridine diphosphate (UDP)‐glucose (Vives‐Corrons, 2000).…”
Section: Diagnosis Of P5′n‐1 Deficiencymentioning
confidence: 99%